γδ T cells and NK cells – Distinct Pathogenic Roles as Innate-Like Immune Cells in CNS Autoimmunity. - MILLS, KINGSTON (My University, 2015)
Multiple sclerosis (MS) is a chronic inflammatory, demyelinating disease that affects the central nervous system (CNS) resulting in progressive cognitive decline and physical disability. Experimental autoimmune encephalomyelitis (EAE) is an animal model of MS that has been used to understand the cellular and molecular mechanisms underlying CNS inflammation and autoimmunity. Since the discovery of IL-17-sereting CD4+ T cells (Th17 cells) over 10 years ago, these cells have been the main focus of attention as mediators of pathology in MS and EAE (1, 2). However, in recent years evidence has emerged that lymphocytes with innate-like properties are potent producers of IL-17 and related pro-inflammatory cytokines (3–6). γδ T cells, NKT, and innate lymphoid cells have been shown to be major sources of IL-17 in host control of a variety of bacterial, viral, and fungal infections. However, dysregulation of these innate-like lymphocytes can also result in severe pathology in EAE and other models of autoimmunity. The role of IFN-γ in the pathogenesis of autoimmune diseases is more controversial
PUBLISHED
Keywords: Autoimmunity; Experimental autoimmune encephalomyelitis; IL-17; Multiple sclerosis; NK cells; γδ T cells; Autoimmunity; Experimental autoimmune encephalomyelitis; IL-17; Multiple sclerosis; NK cells; γδ T cells; Immunology, Inflammation & Infection